The Debt Status of Commercial Company under Gharimin Perspective - Eja Armaz Hardi; Sirajul Arifin; Burhan Djamaluddin (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Currently, commercial entity companies are not regarded yet as one of the groups that receive the zakat. This paper examines the debt status and its micro and macro-economic implications of corporations that experienced the debt shackled in the zakat system through analogy on personal gharim (person in the burden debt). The analysis presented here has been designed on a library research, an analogy method, as well as seen from a debt trap theory. This paper particularly argues that in the twist condition of enterprises to repay their debt, a commercial company may be entitled as the recipient of zakat on behalf of gharim (the fifth group who receives the zakat). It further argues that the loan of the commercial company has a larger impact than individual gharim. Synchronizing the entity companies as â€œsyakhsun iâ€™tibariyunâ€ (the legal person) to the personal obligation to pay zakat is matched to be the reasons for their gharimâ€™s status. The results of this paper contribute to expanding the recipient of zakat on behalf of gharim and enhance the insight of zakat distribution in Islamic philanthropy institutions.